Influence of Export Price, Domestic Sales and Dollar Exchange Value on the Export Volume of Terpentine in Central Java's Non-Wood Forest Products Industry - Muhammad Iqbal Fauzan; Karnowahadi - Karnowahadi; Paniya - Paniya (Admisi dan Bisnis, 2023)
This research aims to identify the influence of export price, domestic sales and Dollar’s exchange rate on Turpentine’s export volume in KBM Industri Hasil Hutan Bukan Kayu Jawa Tengah during 2018-2021. This research was using secondary data during 2018-2021 which obtained by collecting data from KBM Industri Hasil Hutan Bukan Kayu Jawa Tengah and Bank Indonesia. The data was tested with multiplier linear regression analysis technique. F test results indicates that export price, domestic sales and Dollar’s exchange rate simultaneously have a positive and significant influence on Turpentine’s export volume. T test results indicates that export price positively and significantly influence Turpentine’s export volume. Instead, domestic sales and Dollar’s exchange rate have a negative and insignificant influence on Turpentin’s export volume